HIGH-PRESSURE PHASE TRANSITION AND BEHAVIOR OF PROTONS IN BRUCITE MG(OH)2: A HIGH-PRESSURE-TEMPERATURE STUDY USING IR SYNCHROTRON RADIATION - Shinoda K.; Yamakata M.; Nanba T.; Kimura H.; Moriwaki T.; Kondo Y.; Kawamoto T.; Niimi N.; Miyoshi N.; Aikawa N. (My University, 2002)
Infrared absorption spectra of brucite Mg (OH)2 were measured under high pressure and high temperature from 0.1 MPa 25 °C to 16 GPa 360 °C using infrared synchrotron radiation at BL43IR of Spring-8 and a high-temperature diamond-anvil cell. Brucite originally has an absorption peak at 3700 cm-1, which is due to the OH dipole at ambient pressure. Over 3 GPa, brucite shows a pressure-induced absorption peak at 3650 cm-1. The pressure-induced peak can be assigned to a new OH dipole under pressure. The new peak indicates that brucite has a new proton site under pressure and undergoes a high-pressure phase transition. From observations of the pressure-induced peak under various P-T condition, a stable region of the high-pressure phase was determined. The original peak shifts to lower wavenumber at -0.25 cm-1 GPa-1, while the pressure-induced peak shifts at -5.1 cm-1 GPa-1. These negative dependences of original and pressure-induced peak shifts against pressure result from enhanced hydrogen bond by shortened O-H···O distance, and the two dependences must result from the differences of hydrogen bond types of the original and pressure-induced peaks, most likely from trifurcated and bent types, respectively. Under high pressure and high temperature, the pressure-induced peak disappears, but a broad absorption band between 3300 and 3500 cm-1 was observed. The broad absorption band may suggest free proton, and the possibility of proton conduction in brucite under high pressure and temperature.
Keywords: BRUCITE; INFRARED SYNCHROTRON RADIATION (IRSR); IR MICROSPECTROSCOPY; HIGH-TEMPERATURE DIAMOND-ANVIL CELL (HTDAC); HIGH-PRESSURE PHASE TRANSITION; PROTON TRANSFER; SPRING-8